THE PRINCIPAL’S GREEN TRANSFORMATIONAL LEADERSHIP PRACTICES IN SUPPORTING ENVIRONMENT-BASED LEARNING IN KINDERGARTEN - Lina Sundari; Wulan Priyanggani; Dinda Agustiana (JURNAL KOULUTUS, 2026)
Environment-based learning in kindergarten requires leadership capable of integrating an ecological vision into everyday learning practices. This study aims to analyze the principal’s Green Transformational Leadership practices in supporting environment-based learning at Pertiwi Eka Tunas Bhakti Wanacipta Kindergarten. A qualitative approach with a case study design was employed. Data were collected through semi-structured interviews with the principal and two teachers, observations, and documentation. The data were analyzed through data condensation, data display, and conclusion drawing, while data trustworthiness was established through source and method triangulation. The findings indicate that the principal implemented Green Transformational Leadership through four principal practices: translating the school vision into directions for learning, modeling environmentally responsible behavior, encouraging teachers’ creativity in utilizing natural and waste materials, and facilitating reflection while supporting teachers’ ideas and addressing their challenges. These practices supported the use of the surrounding environment as a learning resource while strengthening children’s habituation to environmentally responsible behavior. This study demonstrates that Green Transformational Leadership contributes to the utilization of the surrounding environment as a concrete, accessible, and meaningful learning resource for young children.